Abundance and distribution of microplastics and phthalic acid esters in selected mangrove areas in Peninsular Malaysia / Norkhairah Anuar - Norkhairah , Anuar (2020)
Contamination of microplastics in mangrove has been receiving growing attention as experts reckon 30 billion tonnes of plastics will accumulate in 2050. The vast increase in plastic commodities will increase microplastics abundance in mangroves as mangroves are substantially sinks and traps for plastic debris. Due to persistent properties and high surface to volume ratio of microplastics, Phthalic Acid Esters (PAEs) can be taken up by microplastics, representing a grave threat to the ecosystems. This study investigated the abundance and distribution of microplastics and PAEs in selected mangrove areas in Peninsular Malaysia. The objectives of this study are to identify the anthropogenic activities that may contribute to the abundance of microplastics and PAEs in selected mangrove areas, to determine the abundance and distribution of microplastics and PAEs, and to analyze the relationship associated between them. The prevalence of microplastics and PAEs were studied in six mangrove areas, distributed across the West Coast (Matang, Serkam, and Kukup) and the East Coast (Sedili Besar, Cherating, and Semerak) of Peninsular Malaysia. Anthropogenic activities were identified through observation of 5 km radius surrounding the sampling areas. For sampling of mangrove sediment, three depths from the surface were chosen (1-3 cm, 3-6 cm, and 6-9 cm) at three locations within each mangrove area. Microplastics in surface water were collected using plankton net. The microplastics from sediment were extracted using floatation technique before passing through a set of Tyler sieve of mesh sizes 5.0 mm, 1.0 mm, and 0.5 mm. Likewise, surface water sample was passed through the Tyler sieve of similar aforementioned mesh sizes. The extracted microplastics were treated with 20% alcohol solution overnight and grouped according to size, type, and colour. Soxhlet Extraction and Liquid-liquid Extraction were performed to extract PAEs, followed by GC-MS/MS analysis as the instrumental analysis. Matang, as compared to the other mangroves, has become a subject to high anthropogenic pressure as the area demonstrates the highest number of anthropogenic activities. On average, the highest microplastics concentration in mangrove sediment was found in Matang (65.18 ± 12.34 particles/kg) and in surface water was discovered in Serkam (0.0125 ± 0.0031 particles/m3). The majority of microplastics found in mangrove sediment were 1.0 to 5.0 mm in size, films, with blue and white in colour, whereas most of the microplastics identified in surface water were 0.5 to 1.0 mm in size, fragments, and colour categorized as others. The type of PAEs found were Phthalic acid, bis(7-methyloctyl) ester; 1,2-Benzenedicarboxylic acid, mono(2-ethylhexyl) ester (MEHP); 1,2-Benzenedicarboxylic acid, diisooctyl ester (DIOP); and Decanedioic acid, bis(2-ethylhexyl) ester (DEHS). The total concentration of PAEs recovered from mangrove sediment and surface water were 2060.13 ppm and 670.73 ppm, respectively. Results demonstrated an inverse relationship between microplastics abundance and PAEs concentration in mangrove sediment. This suggests that higher microplastics abundance is observed in sediment with lower PAEs concentration. The findings from this research are vital to set baseline database on microplastics and PAEs pollution, for assessment of future policy measures and as information for managerial actions.